Association between depression and lung function in college students - Wang, Cui; Chen, Hongbo; Shang, Shaomei (Frontiers in Public Health, 2023)
Background Depression is positively associated with lung dysfunction in middle-aged and older adults, but the correlation between depression and lung dysfunction in healthy young adults has not been well researched. Methods This cross-sectional study used a spirometer to evaluate the lung function of 352 college students (mean age: 24.1 years). The spirometry measurements included the peak expiratory flow (PEF), predicted percentage of the peak expiratory flow (PEF pp), forced expiratory volume in 1 s (FEV1), predicted percentage of the FEV1 (FEV1 pp), forced vital capacity (FVC), predicted percentage of the FVC (FVC pp), FEV1/FVC ratio and the predicted percentage of the FEV1/FVC ratio (FEV1/FVC pp). A validated Chinese version of the 20-item Zung Self-rating Depression Scale (SDS) was used to assess the severity of depression among young adults, with scores of ≥40 and ≥ 45 points indicating mild and moderate-to-severe depression, respectively. The Kruskal-Wallis tests were used to analyze the continuous variables, to estimate differences in lung function among the different levels of depression. Chi-square tests or Fisher’s exact tests were used to analyze the categorical variables, to estimate differences in characteristics among the different levels of depression. Several multiple logistic regression models were used to examine the associations between participants’ level of depression and each of the variables measuring lung function. Results Mild and moderate-to-severe depression were observed in 9.9 and 7.4% of the students, respectively. In particular, mild depression was associated with reduced FEV1 in both unadjusted (OR = 1.498, p = 0.003) and adjusted models (OR = 1.290, p = 0.018; OR = 1.199, p = 0.044). On the other hand, moderate-to-severe depression was significantly but negatively related to FEV1 in both unadjusted (OR = 3.546, p = 0.005) and adjusted models (OR = 3.137, p = 0.020; OR = 2.980, p = 0.048). Furthermore, the unadjusted model indicated that mild depression was associated with a higher risk of a lower PEF (OR = 3.546, p = 0.008). Conclusion Severe depression is an independent predictor of decreased FEV1 among Chinese college students.